2016
DOI: 10.1107/s2059798316004903
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a dimerization domain of human Caprin-1: insights into the assembly of an evolutionarily conserved ribonucleoprotein complex consisting of Caprin-1, FMRP and G3BP1

Abstract: Caprin-1 plays roles in many important biological processes, including cellular proliferation, innate immune response, stress response and synaptic plasticity. Caprin-1 has been implicated in several human diseases, including osteosarcoma, breast cancer, viral infection, hearing loss and neurodegenerative disorders. The functions of Caprin-1 depend on its molecular-interaction network. Direct interactions have been established between Caprin-1 and the fragile X mental retardation protein (FMRP), Ras GAP-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 47 publications
6
40
0
Order By: Relevance
“…5D). One of the reasons for this may be direct binding of the scaffolds (27). Taken together, these results supported the observation that S-and R-scaffolds formed distinct substructures in granules and suggested that the scaffolds were not randomly mixed but localized in a moderate order in the granules.…”
Section: Liquid-and Solid-like Rna Granule Formation and Combinationsupporting
confidence: 85%
See 1 more Smart Citation
“…5D). One of the reasons for this may be direct binding of the scaffolds (27). Taken together, these results supported the observation that S-and R-scaffolds formed distinct substructures in granules and suggested that the scaffolds were not randomly mixed but localized in a moderate order in the granules.…”
Section: Liquid-and Solid-like Rna Granule Formation and Combinationsupporting
confidence: 85%
“…This interaction may be mediated by direct binding between specific R-and S-scaffolds, e.g. FMR1 and RNG105 (27). However, such relatively strong binding will inhibit separation of R-and S-substructures if the scaffolds were abundantly expressed, as observed in the cells expressing FMR1 and RNG105 (Fig.…”
Section: Liquid-and Solid-like Rna Granule Formation and Combinationmentioning
confidence: 99%
“…The data presented in this study indicate that miR-193a targets the 3′UTR of Caprin-1 mRNA, leading to inhibition of production of caprin-1 protein. Caprin-1 is known to regulate the cell cycle and cell proliferation 46 47 48 . Caprin-1 directly binds to mRNAs for G3BP1 protein 46 48 , c-MYC (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Caprin-1 is known to regulate the cell cycle and cell proliferation 46 47 48 . Caprin-1 directly binds to mRNAs for G3BP1 protein 46 48 , c-MYC (ref. 47 ) and cyclin D2 through its carboxy-terminal RGG-rich region.…”
Section: Discussionmentioning
confidence: 99%
“…The overall protein fold and dimeric structure assumed by the dCaprin fragments are similar to those of Caprin-1 and Caprin-2 we determined previously (Figure 2A and B). 18 The most noticeable difference between the dCaprin and Caprin-1 or Caprin-2 structures is that the α1 helix in the dCaprin structure is shorter (by about one and a half helical turns) than the one in the Caprin-1 or Caprin-2 structure (Figure 2A and B…”
Section: Data Collection Data Processing and Structure Determinationmentioning
confidence: 99%